The politics of forgetting: Unmaking memories and reacting to memory‐place‐making. (25th March 2021) - Shin, HaeRan; Jin, Yerin
Abstract: This article examines responses to place‐of‐memory making that provoke the memory unmaking practices which constitute the politics of forgetting . Based on in‐depth interviews, participant observations, and archival research the work focuses on two tragic incidents in South Korean history, the May 18 Democratic Uprising in Gwangju in 1980 and the Sewol Ferry disaster on 16 April 2014. In both cases, once the indurate actions of the conservative national governments in power at both times became known, they provoked nationwide anger that precipitated each regime's eventual downfall. Despite widespread outrage, those in government during the respective events had support from right‐wing organisations as well as private citizens both in the actions taken and the ensuing politics of forgetting that enabled them to obscure these two tragedies. We argue that the erosion of memory places using the politics of forgetting exemplified by these two events is the result of each governing party's search for exoneration. By focusing on the positive as well as the negative reactions to the memories in question, this study expands discussions on the diversity of spatial strategies that inform the politics of forgetting and remembering.